2020
DOI: 10.7160/aol.2020.120301
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Evaluation of the User Interface for a Semi-Autonomous Agricultural Robot Sprayer

Abstract: This study presents the heuristic evaluation, as a usability inspection method for Human-Robot Interaction (HRI) systems. First, the methodology to engineer a semi-autonomous agricultural robot sprayer is presented, and then findings from heuristic usability evaluation studies that were carried out on a human-robot interface for a semi-autonomous agricultural vineyard robot sprayer. The following research-based heuristics for the design of robot teleoperation were used: Platform architecture and scalability, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
2
5
0
1
Order By: Relevance
“…In terms of ICT use, the findings supported Sharma et al, (2012), who reported that most of the farmers receive information through cell phones because they are dissatisfied with print media and prefer two-way mobile phone communication. The study's findings were consistent with those of Adamides & Stylianou (2013), who reported that nearly 98 per cent of the farmers in Cyprus used their mobile phones as a source of agriculture information. It was also in line with Roy et al, (2018), who reported that the majority of farmers often used mobile phones (98%) as a main source of communication tools, followed by television (97%), telephones (60%), radio (57%) and the internet (49%) as ICT tools.…”
Section: Utilization Extent Of Ict Toolssupporting
confidence: 88%
“…In terms of ICT use, the findings supported Sharma et al, (2012), who reported that most of the farmers receive information through cell phones because they are dissatisfied with print media and prefer two-way mobile phone communication. The study's findings were consistent with those of Adamides & Stylianou (2013), who reported that nearly 98 per cent of the farmers in Cyprus used their mobile phones as a source of agriculture information. It was also in line with Roy et al, (2018), who reported that the majority of farmers often used mobile phones (98%) as a main source of communication tools, followed by television (97%), telephones (60%), radio (57%) and the internet (49%) as ICT tools.…”
Section: Utilization Extent Of Ict Toolssupporting
confidence: 88%
“…The study by the Cypriot author G. Adamides [21] presented the application of the heuristic evaluation method to test the usability of human-robot interaction systems (HRI) using the example of a semi-autonomous agricultural robot sprayer for vineyards. The following methods were used to design a robot control system: architecture and scalability of the platform, error prevention and recovery, visual design, information presentation, awareness of the robot's condition, efficiency and effectiveness of interaction, awareness of the robot about the environment, and cognitive factors.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Farming is being undertaken by a huge section of population under extremely diverse and changing agro climatic conditions. Mostly, farmers are small and marginal who do not have access to desirable and timely information that adversely affect agricultural growth and productivity [1,2]. All efforts are directed towards the end-users, i.e.…”
Section: Introductionmentioning
confidence: 99%